Lipids and Adipokines in Cord Blood and at 72 h in Discordant Dichorionic Twins. (4th March 2017) - Milenković, Svetlana; Jankovic, Borisav; Mirković, Ljiljana; Jovandaric, Miljana Z.; Milenković, Dušan; Otašević, Biljana
ABSTRACT: Background : Intrauterine growth restriction (IUGR) is a risk factor for developing metabolic syndrome later in life. We explored whether adipokine concentrations in cord blood (CB) and on day 3 (D3) were related to impaired fetal growth and lipids in IUGR twins. Patients and methods : Thirty-six discordant (birth weight [BW] discordance ≥20% calculated in relation to the heavier co-twins) and 42 concordant (BW discordance ≤ 10%) twin pairs were included. Results : In IUGR twins, both adiponectin/BW and triglyceride (TG) levels were significantly higher, while total cholesterol, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol were lower in CB. On D3, both leptin and HDL-C levels were significantly lower and TG levels were significantly higher in IUGR twins. In the discordant group, the alterations in lipids were not related to any adipokine. Conclusions : IUGR is related to lower leptin level and proatherogenic lipid profile (higher TG and lower HDL-C), which are not influenced by adipokine at birth.